Tourist Loyalty Based on Destination Image, Tourist Motivation and Tourist Satisfaction - Eny Endah Pujiastuti; Hastho Joko Nur Utomo; Lintang Laily Nurharumi; Dyah Widowati (Jurnal Bisnis dan Manajemen, 2023)
This study aims to analyze the relationship between destination image, motivation, tourist satisfaction, and tourist loyalty. Data was collected by questionnaire with a sample of 118 tourists who had visited Seribu Batu Songgo Langit tourist destination at least twice with the age of 15-39 years old. SEM analysis is used to test the hypotheses in the proposed conceptual model. Destination Image has a significant influence on Tourist Satisfaction and Tourist Loyalty; Tourist Motivation has a significant influence on Tourist Satisfaction and Tourist Loyalty; Tourist Satisfaction has a significant influence on Tourist Loyalty; Destination Image influence Tourist Loyalty through Tourist Satisfaction; Tourist Motivation influence Tourist Loyalty through Tourist Satisfaction. This study can be useful in the field of tourism/in the area of tourism, both natural and artificial tourism. Novelty/Originality of this study: The results of this study were explored using brand equity theory